2019
DOI: 10.1002/clen.201800380
|View full text |Cite
|
Sign up to set email alerts
|

Microalgae and Clean Technologies: A Review

Abstract: The search for clean technologies needs to be continued to offer alternatives for achieving sustainable energy production and a sustainable economy. This concern is particularly related to the demands of both producing enough renewable energy to meet future needs and reducing greenhouse gas (GHG) emissions. Microalgae are recognized for several benefits they offer, and in recent years, the use of life cycle assessment (LCA) to evaluate the benefits resulting from microalgae cultivation, harvesting/dewatering, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 127 publications
0
6
0
1
Order By: Relevance
“…Identification Scopus and Web of Science (WOS) were used to perform the literature search due to their comprehensive journal coverage, ease of keyword searching, accessibility within academia, and popularity within multiple disciplines (Colares et al, 2020;Souza et al, 2019). The term "Moodle" found articles with a wide range of Moodle topics when used in the search databases, while an initial search of Moodle review articles suggested several keywords, such as "Moodle quiz" and "e-learning".…”
Section: Prisma-p Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Identification Scopus and Web of Science (WOS) were used to perform the literature search due to their comprehensive journal coverage, ease of keyword searching, accessibility within academia, and popularity within multiple disciplines (Colares et al, 2020;Souza et al, 2019). The term "Moodle" found articles with a wide range of Moodle topics when used in the search databases, while an initial search of Moodle review articles suggested several keywords, such as "Moodle quiz" and "e-learning".…”
Section: Prisma-p Processmentioning
confidence: 99%
“…The Vosviewer software, Version 1.6.15, was applied for bibliometric analysis using the Scopus and WOS database search results. Vosviewer is freely available software that automates term identification and constructs bibliometric maps based on network data (Colares et al, 2020;de Souza et al, 2019). The combined downloaded results from Scopus and WOS were used to create a CSV file.…”
Section: Bibliographic Analysismentioning
confidence: 99%
“…This issue must be considered as an important point to manage the whole microalgal production factory with clean energy to achieve environmental sustainability ( Wang et al, 2022 ). The life cycle assessment (LCA) can be used to evaluate the environmental effects and energy concerns, which is an appropriate choice for future improvements in the environmental field ( De Souza et al, 2019 ). According to a previous study, LCAs can be used to show potential ways to prove that applying microalgae contributes to positive feedback to the environment ( Peter et al, 2021 ).…”
Section: Challenges and Future Perspectivementioning
confidence: 99%
“…The settings used in the “VOSviewer” software were the co-occurrence of binary terms and counts, with a minimum number of occurrences of the terms equal to 10, meaning that this term was repeated at least 10 times in the consulted bibliographies. A minimum of 60% for the relevance of the terms was used, following the methodology of Souza et al (2019).…”
Section: Methodsmentioning
confidence: 99%